Analisis Nilai Saksi dalam Proses Pembuktian Menurut Hukum Acara Perdata - Fauziah Lubis; Najwa Ramadhani Lubis; Saidatul Umniyyah; Junita Lubis; Muhammad Fauzan; Muhammad Dzaky Al Muttaqy (Badan Penerbit STIEPARI Press, 2025)
In civil procedural law, witnesses play a crucial role as evidence to clarify disputed facts, especially when written evidence is insufficient. According to Article 164 of HIR and Article 1865 of the Civil Code, witness testimony must be given under oath to gain legal legitimacy. The principle of